ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGGAJIAN KARYAWAN PADA PT TRIDAYA DIMENSI INDONESIA JAMBI - Muhyar, M.; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2019)
Currently PT. Tridaya Dimensi Indonesia grow and develop in terms of labor service providers,especially in Jambi Province by utilizing the development of information technology. But not allinformation system developments are implemented at PT. Tridaya Dimensi Indonesia Jambi, so that theproblem arises in terms of employee payroll. Employee payroll process at PT. Tridaya Dimensi IndonesiaJambi still uses a simple computerized system using Microsoft Excel, so it takes a long time to obtaindetails of payroll data. Therefore the author provides a solution in the form of an Employee PayrollInformation System by using Context Diagrams, Data Flow Diagrams (DFD), and Entity RelationshipDiagram (ERD), as a system design model. For system design, it is only limited to a prototype. Where theresults obtained from this study in the form of Employee Payroll Information System Design at PT.Tridaya Dimensi Indonesia Jambi which can be implemented further so as to produce a payrollinformation system that can support the financial activities of the PT. Tridaya Dimensi Indonesia andemployees.